2017
DOI: 10.1038/s41533-017-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of novel inhaler technique reminder labels on the retention of inhaler technique skills in asthma: a single-blind randomized controlled trial

Abstract: Inhaler technique can be corrected with training, but skills drop off quickly without repeated training. The aim of our study was to explore the effect of novel inhaler technique labels on the retention of correct inhaler technique. In this single-blind randomized parallel-group active-controlled study, clinical pharmacists enrolled asthma patients using controller medication by Accuhaler [Diskus] or Turbuhaler. Inhaler technique was assessed using published checklists (score 0–9). Symptom control was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 33 publications
5
49
0
Order By: Relevance
“…Inhaler technique needs to be delivered in an effective format. Much research has confirmed that patients need to be shown how to use their inhaler, receiving feedback either face-to-face [47] or via video [48], with or without the use of additional tools such as inhaler labels [49] or visual feedback [50]. With this format of educational interventions, we can expect almost all patients to master inhaler technique.…”
Section: What Do Health Care Practitioners Need To Consider In Addresmentioning
confidence: 99%
“…Inhaler technique needs to be delivered in an effective format. Much research has confirmed that patients need to be shown how to use their inhaler, receiving feedback either face-to-face [47] or via video [48], with or without the use of additional tools such as inhaler labels [49] or visual feedback [50]. With this format of educational interventions, we can expect almost all patients to master inhaler technique.…”
Section: What Do Health Care Practitioners Need To Consider In Addresmentioning
confidence: 99%
“…These advantages include large surface area (100 m 2 ), thin (0.1-0.2 mm) physical barriers for absorption, rich vascularization to provide rapid absorption into blood circulation, absence of extreme pH, avoidance of first-pass metabolism with higher bioavailability, fast systemic delivery from the alveolar region to lung, and less metabolic activity compared to that in the other areas of the body (Ali 2010;Lee et al 2018;Yu et al 2016). The local delivery of drugs using inhalers has been a proper choice for most pulmonary diseases (Pison et al 2006), including asthma (Basheti et al 2017;Lavorini et al 2008), cystic fibrosis (Adi et al 2010;Bilton et al 2011), chronic obstructive pulmonary disease (COPD) (Schulte et al 2008;Sulaiman et al 2017), lung infections (Cipolla and Chan 2013;Golshahi et al 2011;Oliveira et al 2017), lung cancer (Zhu et al 2017), and pulmonary hypertension Kanwar et al 2016). In addition to the local delivery of drugs, inhalation can also be a good platform for the systemic circulation of drugs (Moroz et al 2016;Rytting et al 2008;Thwala et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, inhaler technique was significantly enhanced through reinstruction provided to the patients. Incorrect inhaler usage was confirmed by the fact that patients forget the correct technique after a short period of time . Besides, the high rate of incorrect use despite of previous education may be explained by the possibility that physicians and pharmacists may not spend enough time during a busy outpatient clinic or outpatient pharmacy to teach their patients the proper use of the inhaler device.…”
Section: Discussionmentioning
confidence: 99%